Impact of Kisan Call Center in Madhya Pradesh - Kant, Deva; Pandey, Archana (Indian Journal of Extension Education, 2011)
The Kishan Call Center (KCC) has been launched by Ministry of Agriculture, Govt. of India, New Delhi in January 2004. The KCC has been started in all the states of country. The farmers can call up in Kishan Call Center to enquire about queries/problems related to the crops, seeds, fertilizer, insect pest, Horticulture, Veterinary etc. The impact analysis of KCC has been made of 5 years (2006-2010) data on the basis of average calls received at level I, II & III month wise, discipline wise and district wise. On an average the Max Call received in the month September (24455) followed by October (18052) and Min Calls received in the month of January (9887) followed by July (10745). Similarly the Max calls received in percentage (%) in discipline of Plant Protection (50.47) followed by Agronomy (25.93) and Min calls received in percentage (%) in the discipline of Agroforestry (0.07) followed by Soil Science (01.51). The Max calls received in percent (%) from district Jabalpur (20.90) followed by district Narsinghpur (6.20%).The impact analysis shows that the farmers having max problems in kharif crops in the month of September due to reason that crop facing max insect pest problems in this month. It also shows that the farmers awareness is more in insect pest problems in cropping system, than any others problems and then in the discipline of Agronomy mainly regarding availability of seed material, verities and use of fertilizer etc. The farmers have min problems in the month of January because of rabi crops having min insect pest problems etc. as per calls received. On the basis of district wise calls received it shows that the farmers of Jabalpur district are more aware to use the facility of KCC followed by Narsinghpur district. It may be the impact of Agriculture University (JNKVV) Jabalpur.